Contents and Forewords of MIMBAR PENDIDIKAN Journal, Edition of September 2020 - MIMBAR PENDIDIKAN, Editor Journal (MIMBAR PENDIDIKAN, 2020)
MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan (Indonesian Journal for Educational Studies) This journal, with ISSN 2527-3868 (print) and 2503-457X (online), was firstly published on March 11, 2016, by UPI (Indonesia University of Education) Press in Bandung and orgnized by the Lecturers of UPI Journal Developer Team. The MIMBAR PENDIDIKAN is a new version journal from the old journal with the similar name that was published since 1995 to 2005. This journal is dedicated not only for Indonesian scholars who concern about educational studies, but also welcome to the scholars of Southeast Asian countries and around the world who care and share related to the educational studies in general. The MIMBAR PENDIDIKAN journal is published twice a year i.e. every March and September.Bandung, West Java, Indonesia: September 30, 2020.Prof. Dr. Haji Mohammad Fakry GaffarEditor-in-Chief of MIMBAR PENDIDIKAN Journal in Bandung; and Lecturer at the FIP UPI (Faculty of Education, Indonesia University of Education), Bandung, Indonesia. E-mail: mfgaffar@gmail.com